Size and age at first sexual maturity of the edible giant snail adelomelon beckii (Neogastropoda: Volutidae) from Mar Del Plata, Argentina - Arrighetti, Florencia (2010)
The giant volutid Adelomelon beckii (Broderip, 1836) inhabits coastal areas of the western South Atlantic and is distributed from Espíritu Santo, Brazil, to Tierra del Fuego, Argentina, on sandy bottoms between 40 and 70 m (Weaver & Dupont, 1970). This species is one of the top benthic predators found within the studied area (Arrighetti, 2009) and has low population densities (Carranza et al., 2008). The Argentinean populations used to be harvested as part of the bycatch by fishing trawlers, but recently this species has been used for consumption and its large, attractive shell (up to 40 cm SL) sold as an ornament. Despite its impressive size and its increasing significance as a fishery resource, surprisingly little is known about the biology of A. beckii and its role in the ecosystem, except for some aspects of reproduction (Giménez et al., 2009; Arrighetti, 2009; Arrighetti & Giménez, 2010). Sexes are separate, with males having copulatory organs and the females laying egg capsules; each capsule contains 7–9 embryos and is attached to an empty bivalve shell (Penchaszadeh et al., 1999). Adelomelon beckii off Mar del Plata reproduces in spring and autumn (Arrighetti & Penchaszadeh, 2010) and is one of the species of gastropods with highest longevity thus far studied, reaching 29 years old (Arrighetti, 2009). The objective of this study is to describe size and age at first sexual maturity of Adelomelon beckii in the fishing area of Mar del Plata using gonadal maturation studied by histology. These results will then be used to determine minimum catching size in order to establish a future management of this resource.